2019
DOI: 10.1111/jcmm.14378
|View full text |Cite
|
Sign up to set email alerts
|

KLF8 is associated with poor prognosis and regulates glycolysis by targeting GLUT4 in gastric cancer

Abstract: Krüppel‐like transcription factor (KLF) family is involved in tumorigenesis in different types of cancer. However, the importance of KLF family in gastric cancer is unclear. Here, we examined KLF gene expression in five paired liver metastases and primary gastric cancer tissues by RT‐PCR, and immunohistochemistry was used to study KLF8 expression in 206 gastric cancer samples. The impact of KLF8 expression on glycolysis, an altered energy metabolism that characterizes cancer cells, was evaluated. KLF8 showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…SLC2A4 is an efficient glucose transporter that is located in cytoplasmic vesicles and can be transferred to the plasma membrane to take up glucose when stimulated by insulin [ 21 ]. It has been shown that SLC2A4 expression is elevated during cancer progression [ 22 ], 23 ], consistent with our results. SLC2A4 inhibition abolished the biological effects of miR-302b-3p downregulation on inducing the proliferation, migration and invasion of PC cells.…”
Section: Discussionsupporting
confidence: 93%
“…SLC2A4 is an efficient glucose transporter that is located in cytoplasmic vesicles and can be transferred to the plasma membrane to take up glucose when stimulated by insulin [ 21 ]. It has been shown that SLC2A4 expression is elevated during cancer progression [ 22 ], 23 ], consistent with our results. SLC2A4 inhibition abolished the biological effects of miR-302b-3p downregulation on inducing the proliferation, migration and invasion of PC cells.…”
Section: Discussionsupporting
confidence: 93%
“…An accurate prediction of the prognosis of patients with GC plays a very important role in postoperative treatment and follow-up planning. For resectable GC, the prognosis is related not only to the TNM stage (In et al 2017) and biological characteristics (Mao et al 2019;Sun et al 2020;Wang et al 2019) but also to the degree of LND (Degiuli et al 2004;Enzinger et al 2007;Schwarz and Smith 2007) and postoperative comprehensive treatment (Smyth et al 2020). However, so far, except for the extent of lymphadenectomy at the time of gastrectomy, only ELNs and NLNs can reflect the degree of LND to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, T stage is a robust risk factor in GC, which is based on the depth of tumor invasion and can represent the major tumor characteristics. Increasing studies have shown that T stage is not only related to prognosis but also closely related to tumor biological characteristics (Mao et al 2019;Sun et al 2020;Wang et al 2019). Both NLNs and T stage are important independent prognostic factors in GC, which represent the degree of LND and the severity of disease, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Lactate production and glucose consumption were measured by the Lactate Colorimetric Assay Kit (Merck Millipore, MA, USA)) and Glucose Uptake Colorimetric Assay Kit (Sigma-Aldrich, MO, USA), respectively, according to the manufacturer's protocols and previously described (Mao et al 2019 ). RT-PCR was applied to detect the glycolytic enzymes expression levels.…”
Section: Methodsmentioning
confidence: 99%